Strategi Pengembangan Peluang Peran Masyarakat dan Pemerintah Dalam Pengembangan Wisata Budaya Purbakala Situs Megalitikum di Kota Pagar Alam - Dhiniati, Fameira; Mardiansjah, Fadjar Hari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Cultural tourism is a tour where visitors traveling with the purpose of carrying out activities to enjoy cultural attractions, such as ancient. Cultural tourism is almost there in all regions in Indonesia one of Pagar Alam. Pagar Alam has varied tourism potential of one of ancient megalithic sites of cultural tourism. Remains of megalithic sites in Pagar Alam lying spread out and form a very diverse form of statues, dolmen, stone house. The existence of megalithic sites of cultural tourism at this time received less attention, availability of facilities and infrastructure that is not yet complete, as well as promotion and publicity that has been done is still lacking. This study aims to determine the potential role of the public and government's strategy of development of cultural tourism ancient megalithic sites in Pagar Alam. To achieve the objectives of this research method used is descriptive qualitative analysis methods, including analysis of existing conditions, analysis of the role of communities and governments, development analysis, and analysis of tourism development strategy by conducting a SWOT analysis. From the analysis performed that in the development of cultural tourism sites megaitikum many of the problems faced is the lack of coordination and attention from various parties, the limited funds so many poorly-maintained condition megalithic sites, tourism development has not been prioritized. Therefore, the role of government and society is needed in the development strategy of the megalithic sites of cultural tourism, by preparing a program of activities as the proposed development of cultural tourism.